A regionalização da mídia e a Copa do Nordeste: usos e apropriações dos discursos midiáticos de canais esportivos na construção da identidade do torcedor paraibano - Araújo, Ana Flávia Nóbrega (2022)
This research discusses the relation of supporting in Northeastern Brazil from a historical, na economic, and a social construction of hegemonic football, centered on the Rio-São Paulo axis, and the media transmissions that fostered regional inequalities. This work focuses attention on the Northeastern football, which, as of 2013, resumed holding its main tournament: the Copa do Nordeste, making it profitable. To attract the visitors, the broadcasters who transmit the event, Esporte Interativo and Nordeste FC, use imagery-discursive elements based on the Northeastern imaginary. Starting from the paradigm of complexity and from semiotics and discourse analysis, we seek to understand the analyzed phenomenon collectiv identifying as per the regionalized transmissions. As methodological tools, interviews were carried out with fans of three of the four teams from Paraíba State that participated in some edition of the Northeast Cup since its return and with one of the competition's broadcast managers. The research is developed through bibliographic and documentary analysis in the newspapers from Paraíba: O Norte and Jornal A União. It shows that the regionalization movement has provided a new market niche to be explored by different companies, in which customer satisfaction can be acheved. In the sports field, companies that focus their attention on a specific niche use elements rooted in the popular imagination to consolidate themselves in the competitive capitalist market. While fans – even understanding the marketing bias – identify themselves with these uses and foster a movement of resistance in the stands by northeastern football.